"PrEP Gives the Woman the Control": Healthcare Worker Perspectives on Using pre-Exposure Prophylaxis (PrEP) During Pregnancy and Postpartum in Kenya. (June 2022) - Mwongeli, Nancy; Wagner, Anjuli D.; Dettinger, Julia C; Pintye, Jillian; Brown Trinidad, Susan; Awuor, Merceline; Kimemia, Grace; Ngure, Kenneth; Heffron, Renee A.; Baeten, Jared M.; Mugo, Nelly; Bukusi, Elizabeth A.; et al.
Background: Pregnant and postpartum women in high HIV prevalent regions are at increased HIV risk. Oral pre-exposure prophylaxis (PrEP) can decrease HIV incidence reducing infant HIV infections. Understanding healthcare worker (HCW) beliefs about PrEP prior to national roll-out is critical to supporting PrEP scale-up.Methods: We conducted 45 semi-structured interviews among a range of HCW cadres with and without PrEP provision experience purposively recruited from four clinics in Kenya to compare their views on prescribing PrEP during pregnancy and postpartum. Interviews were analysed using a conventional content analysis approach to identify key influences on PrEP acceptability and feasibility.Results: All HCWs perceived PrEP as an acceptable and feasible HIV prevention strategy for pregnant and postpartum women. They believed PrEP meets women's needs as an on-demand, female-controlled prevention strategy that empowers women to take control of their HIV risk. HCWs highlighted their role in PrEP delivery success while acknowledging how their knowledge gaps, concerns and perceived PrEP implementation challenges may hinder optimal PrEP delivery.Conclusion: HCWs supported PrEP provision to pregnant and postpartum women. However, counseling tools to address risk perceptions in this population and strategies to reduce HCW knowledge gaps, concerns and perceived implementation barriers are required.